Event and resistence in the Plague by Albert Camus - Bezerra, Cicero Cunha (2020)
The presence of events as a phenomenon, and its counterpoint, the habit, echo in a continuous interrelationship over the whole plot of the novel The Plague (1947) by Albert Camus. This article consists of investigating the concept of event and its relations with the mediating notion of language - in the same way as the idea of resistance - in the light of a reading of the reflections of Gilles Deleuze, Slavoj Zizek and John Caputo about this subject. Therefore, possible correlations between fictional construction and philosophy will be exposed in the analysis of this work, which is considered one of the most symbolic of the 20th century.